Electrochemical detection of trace silver. (1st April 2021) - Xu, Kequan; Pérez-Ràfols, Clara; Cuartero, Maria; Crespo, Gaston A.
Highlights: State-of-the-art of electrochemical determination of silver during the last decade. Overview of the most relevant potentiometric and voltammetric methods. Critical factors for the improvement of limit of detection and selectivity. Evaluation of possibilities for decentralized analysis implementation. Analysis of recent electrochemical methods for silver speciation. Abstract: Increasing utilization of silver and silver nanoparticles (AgNPs) in daily processes and products has led to a significant growth in scientific interest in methods for monitoring silver. In particular, the amount of silver ions (Ag + ) released to the environment is known to have a detrimental effect on aquatic ecology, and thus some control actions have been implemented in recent years; for example, the manufacturing industry is now required to control and certify the quantity of AgNPs present in products. Electrochemical sensors are well suited to the task of silver monitoring due to several beneficial properties, including low costs, fast measurements, and facile adaptation to miniaturized, portable instrumentation. The predominant method for electrochemical silver determination involves potentiometric ion selective electrodes (ISEs) and voltammetric measurements. Reviewing the literature of the last ten years reveals significant improvements in the analytical performance of electrochemical sensors, mainly related to the development of new protocols, selective receptors, and electrode materials. Remarkably, ISEs with limits of detection (LOD) in the nanomolar range have been reported, employing careful control of ion fluxes across the membrane interfaces. What's more, sub-nanomolar LODs are attainable by stripping voltammetry using either ligand-based deposition strategies or thin layer membranes coupled to conducting polymers. Selectivity has also been optimized through the membrane composition of ISEs, with special focus on Ag + ionophores. Furthermore, novel voltammetric methods allow for discrimination between Ag + and AgNPs. However, there is still a dearth of studies applying such electrochemical sensors to on-site water analysis, and hence, further research is needed in order to translate these laboratory scale achievements to real-world contexts. Overall, this review describes the state-of-the-art in electrochemical silver detection, and provides a comprehensive description of those aspects contributing to the further development and improvement of analytical performance. Graphical abstract: Image, graphical abstract